Perancangan Pengukuran Kinerja di PT Indocement Tunggal Prakarsa Tbk. Menggunakan Baldrige Excellence Framework 2015-2016 - Almandri Nur Putra; Arief Daryanto; Sahara Sahara (School of Business, Bogor Agricultural University (SB-IPB), 2018)
Nowadays, Indonesia cement industry is facing a dissatisfactory condition. The national cement competition landscape has been changed. There are some new cement producers crowded out the industry. At the time, they can corrupt the market share of the existing players, including PT. Indocement Tunggal Prakarsa Tbk. as one of the biggest cement producers in Indonesia. To overcome this problem, one of the best solutions is to improve the performance, and it can be started with a favorable performance measurement system. This study used a well-known performance measurement tool of Baldrige Excellence Framework (BEF) of 2015-2016. This study aims to define the criteria of the Baldrige Excellence Framework of 2015-2016 of PT Indocement Tunggal Prakarsa, Tbk, to assess the performance based on the Baldrige Excellence Framework of 2015-2016, and to give strategic and exact suggestions on the company performance measurement, based on the strength and opportunity for improvement and BEF scoring result. Based on the result of this study, PT. Indocement Tunggal Prakarsa Tbk. scored 423.91 points indicating that the company is classified as Global Average class for its global performance criteria with the predicate of Early Improvement. This means that performance of the company has to be improved in any fields to strive an excellence company within all criteria.Keywords: BEF, performance measurement, performance improvement, cement, PT Indocement